Laparoscopic Redo Pyeloplasty After Failed Open Surgery - Shadpour, Pejman; Haghighi, Ramin; Maghsoudi, Robab; Etemedian, Masoud (Urology Journal, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Purpose: To report our experience in treating patients with failed previous open pyeloplasty by transperitoneal laparoscopic pyeloplasty. Materials and Methods: Eleven patients with previous failed open pyeloplasty were reviewed, all of whom had undergone transperitoneal laparascopic pyeloplasty. All procedures were performed by a single team. Depending on the anatomic situation, either dismembered or a flap technique was utilized. Subsequent follow-up was by ultrasonography initially, and diuretic renal scintigraphy and/or intravenous urography at least 12 months after the re-operation. Data were collected from the medical records. Results: The study group consisted of 7 men and 4 women with the mean age of 41.4 years (range, 27 to 55 years). Mean operation time was 208 minutes (range, 165 to 250 minutes) and mean hospital stay was 3.6 days (range, 3 to 5 days). Mean follow-up was 24.1 months (range, 12 to 42 months). The overall success rate for these salvage laparoscopic pyeloplasties was 90.9%. Only one female patient developed dull flank pain 3 months after stent removal. There was no conversion to open surgery. None experienced major complications or required blood transfusion. Conclusion: Laparoscopic pyeloplasty can be a valid and feasible option in treating patients with failed prior open pyeloplasty.